EFFECT OF WORK ETHICS AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE WITH INTERVENING VARIABLE ORGANIZATIONAL COMMITMENT - Rika Kartika; Jufrizen Jufrizen (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study is to determine and analyze the Effect of Work Ethics and Job Satisfaction on Employee Performance and Organizational Commitment as Intervening Study Variables at the North Sumatra Governor's Office of the Economic Bureau directly or indirectly. The approach used in this study is an associative approach. The population in this study was all employees of the North Sumatra Governor's Office, which amounted to 60 people. Data collection techniques in this study used interview techniques, documentation studies, observations, and questionnaires. The data analysis technique in this study uses a quantitative approach using statistical analysis using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Test. Data processing in this study used a PLS (Partial Least Square) software program. The results of this study prove that directly organizational culture and job satisfaction Work Ethics and job satisfaction have a positive and significant effect on employee performance through intervening variables of organizational commitment of the North Sumatra Governor's Office of the Economic Bureau. In other words, organizational commitment does play a role as amediator.